Pengaruh Harga Kamar Dan Fasilitas Kamar Terhadap Kepuasan Tamu Di Rocky Plaza Hotel Padang - Ivan Kolivanof; Feri Ferdian (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the effect of room rates and room facilities on guest satisfaction at Rocky Plaza Hotel Padang. This type of research is quantitative descriptive research with causal associative methods. The population in this study is consumers who have visited Rocky Plaza Hotel Padang with a sample of 354 respondents. The data in this study used primary data and secondary data. The research instrument uses questionnaires arranged according to the Likert scale.instrument trials use validity tests and reliability tests. Data were analyzed using data metabulation and descriptive data. The results of this study are that room prices at Rocky Hotel Padang show a good category with 67.57%, the level of achievement of respondents in the room price variable is at 67.57% which is categorized as good, which is in accordance with the level of respondents' achievements which are at 66% - 85% is declared a good category. Room facilities at Rocky Hotel Padang show a good category with 66.28%, the level of achievement of respondents in the variable room price is at 66.28% which is categorized as good, which is in accordance with the level of respondents' capian which is at 66% - 85% is declared a good category. The decision to stay at Rocky Hotel Padang shows a sufficient category with 60.93%, the level of achievement of respondents in the variable decision to stay is at 60.93% which is categorized as good, which is in accordance with the level of respondents' achievements which are at 66% - 85% is declared good. Room rates have a positive and significant effect on the decision to stay at Rocky Hotel Padang. Room facilities have a positive and significant effect on the decision to stay at Pangeran City Hotel Padang.